Coastal Macroinvertebrate Study in Penang Island, Malaysia - Chee Su Yin; Sim Yee Kwang (Tropical Life Sciences Research, 2016)
Land reclamation in Penang began two decades ago and is still rampant with large reclamation projects planned to be executed in the near future. The present study provides the first information on effects of land reclamation in Penang towards the coastal macroinvertebrates. This study assessed the abundance, diversity, and evenness of coastal invertebrates assumed to be the foremost affected when land is reclaimed. Three kinds of areas were focused on: reclaimed, unclaimed (adjacent to reclaimed), and undisturbed. A total of 53 species of macroinvertebrates from 10 classes (Gastropoda, Bivalvia, Polychaeta, Malacostraca, Maxillopoda, Echinoidea, Polyplacophora, Branchiopoda, Scaphopoda, and Holothuroidea) were sampled. Reclaimed areas were moderately rich in species averaging 11 species compared to 7 species in adjacent and 14 in undisturbed areas. Species richness was the highest in Teluk Aling (an undisturbed area) with 22 species, and was the lowest in Gurney Drive (an adjacent area) with 2 species. The average species diversity and evenness on reclaimed land was the lowest with values of 1.9974 and 0.5787, respectively. The diversity was higher by 5.07% in adjacent areas and by 22.92% in undisturbed areas compared to reclaimed areas. Species evenness was 29.75% higher in unreclaimed areas and 17.87% higher in undisturbed areas compared to reclaimed areas. Land reclamation reduces species diversity and evenness, and to a lesser extent, species richness.